Multiyne chains chelating osmium via three metal-carbon σ bonds. Issue 1 (December 2017) - Zhuo, Qingde; Lin, Jianfeng; Hua, Yuhui; Zhou, Xiaoxi; Shao, Yifan; Chen, Shiyan; Chen, Zhixin; Zhu, Jun; Zhang, Hong; Xia, Haiping
Abstract Although the formation of metal–carbon σ bonds is a fundamental principle in organometallic chemistry, the direct bonding of one organic molecule with one metal center to generate more than two metal–carbon σ bonds remains a challenge. Herein, we report an aromaticity-driven method whereby multiyne chains are used to construct three metal–carbon σ bonds in a one-pot reaction under mild conditions. In this method, multiyne chains act as ligand precursors capable of chelating an osmium center to yield planar metallapolycycles, which exhibit aromaticity and good stability. The direct assembly of various multiyne chains with commercially available metal complexes or even simple metal salts provides a convenient and efficient strategy for constructing all carbon-ligated chelates on the gram scale. Metal-carbon σ bonds mark the basis of organometallic chemistry, but the formation of multiple such bonds between single organic and metal entities remains a challenge. Here, the authors report a one-pot aromaticity-driven method to construct osmium-based multidentate complexes containing three metal-carbon σ bonds from multiyn chains.